2015
DOI: 10.7182/pit2015957
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Frequent Internet Use in an Urban Kidney Transplant Population in the United States: Characterizing the Digital Divide

Abstract: Alternatives to electronic information sources and/or additional resources should be considered for those who may fall in the so-called digital divide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
2
11
1
Order By: Relevance
“…The sample characteristics and methods of the 2012 technology survey were like the 2016 survey and can be found elsewhere. 13 , 14 All participants provided informed consent before participation in the study. Both studies were approved by the University of Chicago Institutional Review Board before the administration of the study survey and conducted in adherence with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample characteristics and methods of the 2012 technology survey were like the 2016 survey and can be found elsewhere. 13 , 14 All participants provided informed consent before participation in the study. Both studies were approved by the University of Chicago Institutional Review Board before the administration of the study survey and conducted in adherence with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work characterizing device ownership trends and attitudes related to ICT in prekidney and postkidney transplant patients represented a narrow window into the many nuances of technology use in this chronically ill population. 13 , 14 In our 2012 technology survey of prekidney and postkidney transplant patients, we found a significant disparity among racial/ethnic minorities particularly with regard to frequent Internet use, defined as using the Internet more than 5 hours per week. 13 In addition, we found that device ownership and frequency of technology use were less in our prekidney and postkidney transplant population than what had been previously reported in an earlier national survey of people with one or more chronic health conditions in the United States.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This inequality leads to disparities in the outcomes from the IT investments and their use, called 'digital outcome divide' [12]. In the healthcare literature, disparities in patients' access to or use of IT has been repeatedly reported in various clinical contexts including transplant [31,32,33,34,35]. African-American patients register for the use of a web portal less frequently than other ethnic groups [33], and patients with a higher education level (college or higher) use a patient portal more frequently than those with a lower education level [35].…”
Section: Expected Impacts Of Patient Portalsmentioning
confidence: 99%
“…This phenomenon called the 'Digital Divide,' has been repeatedly reported by research studying health IT. The difference in the distribution of patients' Internet use and access is attributed to ethnicity and level of education [32,31]. Despite the high Internet accessibility, African-American patients enroll in a patient portal less frequently than white patients [33,34], and patients with a college degree or higher use a patient portal more frequently than those with a high school degree or lower [35].…”
Section: Stratified Analysis By Ethnicity and Educationmentioning
confidence: 99%